2014
DOI: 10.3390/nu6031236
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hypertriglyceridemia in the Development of Atherosclerosis and Endothelial Dysfunction

Abstract: A hereditary postprandial hypertriglyceridemic rabbit (PHT rabbit) is a new dyslipidemic model showing remarkably high plasma triglycerides with only limited elevation of plasma total cholesterol. In PHT rabbits, plasma triglyceride was markedly elevated postprandially compared with healthy Japanese white (JW) rabbits. In physiological experiments, the ring preparation of the thoracic aorta was suspended in an organ bath filled with modified Krebs-Henseleit solution, and the developed tension was recorded. End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
(36 reference statements)
1
32
0
Order By: Relevance
“…A number of HDL constituents may interact with the vascular endothelium (41,42). Various of studies have reported that elevated TG, TC, LDL and VLDL levels and decreased HDL levels may serve a role in the development of endothelial damage and vascular dysfunction (43,44). Obesity, which is primarily caused by intake and storage of nutritional substrates, is an important public health issue (45).…”
Section: Discussionmentioning
confidence: 99%
“…A number of HDL constituents may interact with the vascular endothelium (41,42). Various of studies have reported that elevated TG, TC, LDL and VLDL levels and decreased HDL levels may serve a role in the development of endothelial damage and vascular dysfunction (43,44). Obesity, which is primarily caused by intake and storage of nutritional substrates, is an important public health issue (45).…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial lipemia is hypothesized to be a risk factor for cardiovascular disease by inducing endothelial dysfunction [20]. The vascular endothelial lining functions to maintain adequate blood flow and regulate coagulation and inflammation.…”
Section: Role Of Postprandial Lipemia In Endothelial Inflammation Andmentioning
confidence: 99%
“…Postprandial hyperlipidemia is characterized by triglyceride-rich lipoproteins (TRL) such as chylomicrons, very low-density lipoproteins and their remnants. Both endothelial dysfunction and elevated plasma triglycerides are thought to play important roles in atherosclerosis [26; 27; 28; 29; 30; 31; 32; 33; 34; 35], but the influence the lens effect may have on NO bioavailability, however, does not appear to have been fully considered. At a constant rate of endothelial NO production, increased NO consumption within TRL could decrease the amount of NO available for direct vasodilation and proper endothelial function.…”
Section: Introductionmentioning
confidence: 99%